Ethnopedagogy and Mathematics Learning Outcomes: Evidence from Ende Traditional House Miniatures - Ummu Fajariyah Akbari; Maria Veronika Mentari Lami; Uslan Uslan; Ahmad Yani (Borneo Research and Education Center, 2026)
The current research aims to develop and validate an ethnopedagogical material based on Ende traditional house miniatures to support elementary school students' mathematics achievement in Kupang, Indonesia. A research and development design was used involving experts, teachers, and students. Two experts are rating the content validity of the media; a teacher and ten students are confirming the practicality of the media. A survey instrument was used to examine the content validity and practicality of the media, and a test was used to examine students' mathematics achievement. The data analysis was carried out in JAMOVI software, involving the content validity index and descriptive analysis. Preliminary observations indicate the need to develop and implement appropriate and accessible learning media to support both teaching practices and students’ mathematics achievement. The result confirms the initial content validity of the media, shown through the expert agreement that confirms the structure of the media, alignment of the media with syllabi and material, and the miniature of the media. The finding also confirms the preliminary practicality of the media through teachers' agreement on the media's attractiveness, usability, and content clarity. Other than that, the students agree on the preliminary practicality of use of the media, interest and feelings about using the media, and the effect of the media on their comprehension and ability to answer mathematics questions. Furthermore, the mean difference between the pre-test and post-test of students in using the media indicates the initial improvement of the students' scores. Therefore, this media is recommended for use in primary-level mathematics education to improve both teaching practices and student learning outcomes. However, this research did not use experimental design to test the empirical effect of the media. Hence, future research is suggested to examine the media through a more robust research design.